Socio-demographic risk factors for unintended pregnancy among unmarried adolescent Nigerian girls - Chibuogwu Izugbara (South African Family Practice, 2015)
Background: Globally, unintended births among unmarried adolescent girls are a major contributor to maternal and childhood mortality, the vicious cycle of ill-health, poverty, and truncated educational opportunities. Nigeria has the highest rates of adolescent fertility in sub-Saharan Africa. Over 900 000 births to adolescents occur annually and 150 out of every 1000 women who give birth in Nigeria are 19 years old or under.